2017
DOI: 10.1007/s11250-017-1461-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of African swine fever virus and classical swine fever virus antibodies in pigs in Benue State, Nigeria

Abstract: This study investigated the prevalence of African swine fever virus (ASFV) and classical swine fever virus (CSFV) antibodies in pigs in Benue State, Nigeria. Serum samples were collected from a total of 460 pigs, including 416 from 74 piggeries and 44 from Makurdi slaughter slab. The samples were analysed using indirect enzyme-linked immunosorbent assay (ELISA) test kit to detect the presence of ASFV antibodies, while competitive ELISA test kit was used to detect antibodies to CSFV. Our findings showed a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…ASF is endemic in Southwest Nigeria and the results of the present study is far lower than 28% reported by Awosanya et al (2015) with higher prevalence during the dry season compared to rainy season. On the contrary, a total seroprevalence of 2.8% was reported in Benue which is further delineated into two categories, prevalences of 7 (1.7%) and 6 (13.6%) were observed in piggeries and in Makurdi slaughter slab, respectively (Asambe et al, 2018). It seems there is less prevalence at piggery pen than slaughter slabs.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…ASF is endemic in Southwest Nigeria and the results of the present study is far lower than 28% reported by Awosanya et al (2015) with higher prevalence during the dry season compared to rainy season. On the contrary, a total seroprevalence of 2.8% was reported in Benue which is further delineated into two categories, prevalences of 7 (1.7%) and 6 (13.6%) were observed in piggeries and in Makurdi slaughter slab, respectively (Asambe et al, 2018). It seems there is less prevalence at piggery pen than slaughter slabs.…”
Section: Discussionmentioning
confidence: 86%
“…The detection of antibody against ASF was carried out by indirect Enzyme-linked immunosorbent assays (ELISA) as recommended by the manufacturer (IDvet,310, rue Louis Pasteur-Grabels-FRANCE). ELISA was carried out in a 96-well plate as described in previous study (Asambe, Sackey, & Tekdek, 2018). Briefly, 100 µl of dilution Buffer 14 to each well, which was followed by addition of 10 µl of the negative control buffer (supplied with the kit) to wells A1, B1 and A2, and B2.…”
Section: Antibody Detection Testmentioning
confidence: 99%
“…This study further reveal that the farmers are small scale farmers and as such generally have small flock size and hence family labour may be adequate. The low herd size may also be partly due to the common disease challenges faced by the pig industry in Benue State, especially the regular outbreaks of contagious diseases, such as ASF (Asambe et al, 2017). In fact, the high mortality rate of these diseases (close to 100% for ASF) in affected farms causes farm owners either to remain only with the few survivors, to restock the farms with few animals or to take less risk in investing for a larger farm (Kouam and Moussala, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Combining farm-mixing of feeds and kitchen wastes may be more economical than using commercial feeds alone. However, kitchen wastes are not properly heated before feeding it to animals, the risk of transmitting diseases such as African Swine Fever (ASF) among other diseases is high (Asambe et al, 2017). Purchasing replacement stock for breeding within the same locality predisposes to inbreeding and subsequently low production, reproduction and poor health (Kirima et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…1. Rome: Food and Agriculture Organization of the United Nations 2012; Andriamanivo et al 2019;Asambe et al 2017;Costard et al 2009;Fasina et al 2012;Randrianantoandro et al 2015). The challenge is how to mitigate the risks to reduce or eliminate losses due to ASF and make smallholder pig production more profitable and sustainable.…”
Section: Trends and Challenges For Controlmentioning
confidence: 99%